Assessment of Knowledge, Attitudes and Practices Relating to Parasitic Diseases and Anthelmintic Resistance Among Livestock Farmers in Hamedan, Iran - Sazmand, Alireza; Alipoor, Golnaz; Zafari, Salman; Zolhavarieh, Seyed Masoud; Alanazi, Abdullah D.; Sargison, Neil D. (Frontiers in Veterinary Science, 2020)
Iranian studies have shown a high prevalence of broad spectrum anthelmintic resistance (AR) in gastrointestinal helminths of ruminants. However, there is a lack of information about levels of knowledge, attitudes and practices among livestock farmers in Iran regarding the concept of parasite control and AR. This study aimed to evaluate the knowledge, attitudes and practices of livestock farmers of Hamedan, Iran, regarding parasitic diseases and AR by interviewing 150 farmers using a structured questionnaire. Most of farmers had some knowledge of the clinical signs associated with helminth parasitism, but more than half were unaware of the existence of zoonotic parasites. More than half of the participants had never heard about AR, but were interested to learn about it through their veterinarians. Those who were aware of the problem considered non-prescribed anthelmintic drugs to play a role in its emergence, while several of the participants believed that ‘more expensive’ and ‘foreign-branded’ drugs worked best. Almost all of the farmers reported that they frequently consulted with a veterinarian about anthelmintic treatments, but very few adhered to recognised principles of responsible and sustainable drug use. About half of the participating farmers treated their sheepdogs for helminth parasites, despite the common practice of regularly feeding likely infected livestock offal. Education had a significantly positive association with farmers’ knowledge, attitudes and best practice scores, while knowledge was significantly associated with both attitudes and practices. Based on these results, we recommend that regular country-wide classes should be held to educate farmers on the evidence-based principles of sustainable helminth control and prevention of zoonotic helminth diseases.